The Accuracy of Nurses’ Predictions for Clinical Outcomes in the Chronically Critically Ill - Lipson, Amy R (Res Rev J Nurs Health Sci, 2017)
BACKGROUND: Accurately predicting survivorship of patients in the intensive care unit is known to be difficult. Previous research has shown that nurses are more likely to recognize futile medical care than other disciplines. The purpose of this study was to describe the accuracy of nurse’s predictions for survival of patients who are chronically critically ill (CCI). METHODS: Using a secondary data analysis from a longitudinal, descriptive study, we evaluated nurses’ predictions for survival at admission and until ICU discharge or patient death. RESULTS: Nurses were able to more accurately predict survival of CCI patients than death and prognostication appeared to improve with prolonged ICU stays. CONCLUSION: This is the first longitudinal study that focused on nurse prognostication in a chronically critically ill patient population. Future research should explore the relationship between ICU nurse characteristics and the accuracy of survival predictions.